Cephalic Index among Nepalese Medical Students - Manandhar, Bipana (Orthodontic Journal of Nepal, 2017)
Introduction: Cephalic index is race and sex specific parameter. Morphology of all living beings undergoes changes in varying degrees during their life and the features are variable in the individuals of the same species. Objective: To measure the head size of the Nepalese medical students of both sexes between 18 to 24 years of age, to determine the different head type and to explore the distribution of cephalic index by ethnicity. Materials & Method: Materials used were a Spreading caliper and a measuring scale. The method used for assessing cephalic index was Hrdlicka’s method. Result: The result showed that the majority of the medical students of Nepal Medical College had typical Brachycephalic head type. Conclusion: The dominant type of head shape revealed was brachycephalic and the least common head type as Dolicocephalic in Nepalese medical students of all the three ethnic groups namely Brahmin, Newar and Chettri.